Mechanisms in endocrinology maternal thyroid dysfunction during pregnancy and behavioural and psychiatric disorders of children: A systematic review - Fetene, D.; Betts, K.; Alati, Rosa (BioScientifica, 2017)
© 2017 European Society of Endocrinology. Background: Maternal thyroid dysfunction during pregnancy may lead to persistent neurodevelopmental disorders in the offspring appearing in later life. This study aimed to review the available evidence concerning the relationship between maternal thyroid status during pregnancy and offspring behavioural and psychiatric disorders. Methods: Systematic electronic database searches were conducted using PubMed, Embase, PsycNET, Scopus, Google Scholar and Cochrane library. Studies including gestational thyroid dysfunction as the exposure and offspring behavioural and psychiatric disorders as the outcome were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed and, after thorough screening by two independent reviewers, 13 articles remained eligible for inclusion in this study. Results: Indicators of maternal thyroid dysfunction, including low and high thyroid hormone level and autoimmune thyroiditis, during early pregnancy, were found to be associated with several offspring behavioural and psychiatric disorders such as attention deficit hyperactivity disorder (ADHD), autism, pervasive developmental problems, externalising behaviour, in addition to epilepsy and seizure. The majority of associations were found with low maternal thyroid hormone level. Conclusion: Maternal thyroid function during pregnancy, particularly hypothyroidism, is associated with behavioural and psychiatric disorders in children. Further studies are needed with a capacity to adjust for a fuller range of confounding factors.